WTO DISPUTE SETTLEMENT MECHANISM: INDONESIA’S PROSPECTIVE IN INTERNATIONAL TRADING SYSTEM - Mrs. Koesrianti (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2015)
A rule-based system of World Trade Organization (WTO) should be supported by effective mechanism of disputes that ensure the Dispute Settlement Body (DSB) rulings toward the respondent could be enforced. The WTO DSM aims to provide predictability and security in international trade by providing strict time-frames, and was designed to be mutually agreed by the disputing members, flexible and binding. For the developing countries in the WTO, they need major effort in terms of training and institutional reform to meet the challenges of participation in the WTODSM. Indonesia has involved in the WTODSM. Sistem perdagangan WTO harus didukung oleh mekanisme penyelesaian sengketa yang efektif. Kepatuhan pada putusan Dispute Settlement Body (DSB) sangat penting agar manfaat perdagangan dapat dirasakan oleh seluruh anggota WTO, termasuk negara-negara berkembang. Dispute Settlement Understanding (DSU) WTO memberikan keamanan dan prediktabilitas atas proses sengketa di WTO yang dibutuhkanoleh seluruh anggota WTO sehingga memberikan kesempatan luas bagi negara-negara anggota WTO untuk berpartisipasi dalam mekanisme penyelesaian sengketa di WTO, termasuk Indonesia.